Keragaman Jamur Mikoriza Arbuskular pada Rizosfer Tiga Varietas Tanaman Tebu: Diversity of Arbuscular Mycorrhizal Fungi in the Rhizosphere of Three Sugarcane Varieties - Zulfa Fatmawati; Jaka Widada; Donny Widianto; Anjar Cahyaningtyas; Devanda Ayu Lidya Permata Putri (Acta Solum, 2025)
Arbuscular mycorrhizal fungi (AMF) form associations with more than 80% of the terrestrial plants. These associations enhance nutrient sequestration and plant resistance to environmental stress. The diversity of AMF is highly influenced by the host plants. The types of AMF in the Bululawang, Kidang Kencana, and Pasuruan Jengkol 922 sugarcane varieties grown in a similar location were identified through morphological and molecular methods. AMF spores were isolated by the wet sieving method. The morphological features of the AMF spore mounted in PVLG and Melzer’s reagent were observed under a microscope. The DNA of the fungi was extracted, and the ribosomal RNA genes were amplified by nested PCR with the NS1-NS4 primer pairs, followed by the AML1-AML2 primer pairs. A moderate diversity of AMF was observed, with a total of 269 spores found in the Kidang Kencana variety, 191 spores in the Bululawang variety, and 142 spores in the Pasuruan Jengkol 922 variety. Four AMF species have been identified morphologically and molecularly, namely Glomus flavisporum, Acaulospora koskei, Gigaspora Margarita, and Scutellospora savannicola. These findings indicate that the number and type of AMF associated with sugarcane roots are influenced by plant varieties, in which the Glomus sp. is the dominant species in the three sugarcane varieties studied.